2018
DOI: 10.1103/physrevd.97.104019
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium configurations of a charged fluid around a Kerr black hole

Abstract: Equilibrium configurations of electrically charged perfect fluid surrounding a central rotating black hole endowed with a test electric charge and embedded in a large-scale asymptotically uniform magnetic field are presented. Following our previous studies considering the central black hole non-rotating, we show that in the rotating case, conditions for the configurations existence change according to the spin of the black hole. We focus our attention on the charged fluid in rigid rotation which can form toroi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The tori are modeled as "dielectric" structures under assumption of zero conductivity, being thus complementary to the"force-free" structures constructed under assumption of infinite conductivity that are frequently used in the literature. The levitating charged structures could be, in dependence on the character of the external magnetic field, clouds located at the spacetime symmetry axis [19,82], or tori orbiting around the axis [18,83]. Clearly, in both cases, the off-equatorial charged non-conducting structures could potentially serve as the "lamp models" for irradiation of equatorial disks in the generation of profiled spectral lines [84].…”
Section: Role Of Magnetic Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tori are modeled as "dielectric" structures under assumption of zero conductivity, being thus complementary to the"force-free" structures constructed under assumption of infinite conductivity that are frequently used in the literature. The levitating charged structures could be, in dependence on the character of the external magnetic field, clouds located at the spacetime symmetry axis [19,82], or tori orbiting around the axis [18,83]. Clearly, in both cases, the off-equatorial charged non-conducting structures could potentially serve as the "lamp models" for irradiation of equatorial disks in the generation of profiled spectral lines [84].…”
Section: Role Of Magnetic Fieldsmentioning
confidence: 99%
“…Usually, the charged fluids are considered as a plasma constituted by protons (ions) and electrons, treated in the approximation of infinite conductivity. On the other hand, in our previous works [18,19,43,82], the idea of modeling charged fluid tori in the opposite limit-the limit of zero conductivity, was introduced. Assuming the Kerr (Schwarzschild) black hole backgrounds and the uniform or dipole external magnetic fields are weak enough to have a negligible effect on the spacetime structure, it was shown that the equatorial charged fluid tori are able to form complex structures demonstrating phenomena interesting from the astrophysical and observational points of view; in some cases, the charged non-conducting tori can constitute even double equatorial toroidal structures that can be accompanied by the off-equatorial ones or by the cloud formations [18,19].…”
Section: Charged Fluid Structures Circling Around Magnetized Compact mentioning
confidence: 99%
“…Particularly in what concerns the relativistic geometrically thick accretion discs, most of the previous works are mainly devoted to equilibrium toroidal configurations. That is, the flow restricted to the azimuthal component only, with assumption that the radial and meridional components are negligible in comparison with the azimuthal one (Banerjee et al 1997; Kovar et al 2011; Trova et al 2018). Similar to our idea, both in Newtonian regime (Tripathy, Prasanna, & Das 1990) and in relativistic regime for a non-rotating Schwarzschild black hole without the vertical component for the magnetofluid velocity (Shaghaghian 2016), already have been done.…”
Section: Introductionmentioning
confidence: 99%
“…It is the scenario of a fluid with global non-zero charge and pure convective transport of charge across background magnetic field lines. Within this approximation, a general relativistic model for the rotating charged fluid can be constructed and tested in various scenarios [10][11][12][13][14][15][16]. By choosing proper background gravitational and electromagnetic fields, i.e.…”
Section: Introductionmentioning
confidence: 99%